Prevalence of chlamydia and gonococcal infection in women assisted in the STI clinic of Alfredo da Matta Foundation, Manaus, Amazon - Benzaken, Adele Schwartz; Sales, Drielle N.; Palheta Junior, Jamile I.L.; Pedrosa, Valderiza L.; García, Enrique G. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: the weak correspondence between the syndrome of vaginal or cervical discharge and gonococcal or chlamydial infection has been widely reported. Therefore it is necessary to find new elements permitting to improve the diagnostic. Objective: to estimate prevalence and risk factors associated with gonococcal and chlamydial infection in symptomatic and asymptomatic women who sought care in a STI clinic and to evaluate the performance of risk assessment score for vaginal discharge, actually used in Brazil. Methods: in 2008, 239 women, symptomatic and asymptomatic for vaginal discharge, were recruited in the STI clinic of Fundação Alfredo da Matta in Manaus, State of Amazon, and tested for Chlamydia trachomatis e Neisseria gonorrhoeae. Results: prevalence for chlamydial infection (DNA hybridization) was 13.0%, for gonococcal cervical infection 7.1% (Thayer Martin), for coinfection 12.9% and 18.4% to have either one of them. Highest prevalence were found in adolescents and women who had a partner presenting urethral discharge in the past, this being the only significant predictor in multivariate analysis for gonococcal infection [OR = 4.8 (2.2-10.5)]. Symptomatic women with a positive risk score (≥ 2) showed only significantly higher prevalence for gonococcal infection (p < 0.001). Evaluation of sensibility, specificity and PPV for the Brazilian risk assessment score showed low values and therefore not contribute to decrease the proportion of unnecessary treatments. Conclusion: chlamydia is the most prevalent infection among the women seeking for care at the STI clinic, and 58% of them were asymptomatic cases. Having a partner with urethral discharge represents the only independent variable for gonococcal infection or for those with coinfection, but not specifically for chlamydial infection. The risk assessment score showed insufficient sensitivity and specificity to detect cervical infection with chlamydia and gonorrhea or both.